Factors influencing disease-induced mortality of Pacific oysters Crassostrea gigas - Petton, Bruno; Boudry, Pierre; Alunno-Bruscia, Marianne; Pernet, Fabrice (Aquaculture Environment Interactions, 2015)
Mortalities of oyster Crassostrea gig-as seed associated with ostreid herpesvirus OsHV-1 mu Var have been observed in many oyster-producing countries since 2008. The present study, comprised of 4 complementary experiments, aimed to identify factors associated with disease-induced oyster mortality in order to propose mitigation strategies. Our first experiment compared survival of oysters from natural spatfall with others sampled from nurseries, after thermal elevation in the laboratory from <14 to 21 degrees C. A total of 60% of the tested wild seed batches (n = 51) were infected by OsHV-1, exhibited mortality and were able to transmit the disease to cohabited naive oysters. Comparatively, only 1 out of the 32 tested batches sampled from nurseries presented similar characteristics. In a second experiment, we studied the effects that timing and duration of exposure to field conditions had on risk of infection and mortality in the laboratory at 21 degrees C. Naive oysters deployed in the field during winter and spring, when seawater temperatures were <14.7 degrees C, showed no mortality in the laboratory, and OsHV-1 DNA was not detected by PCR. However, in oysters transferred to the field, OsHV-1 was observed when seawater temperature reached similar to 15.3 degrees C. Our third experiment showed that the odds of mortality decreased with age of oysters when facing the disease. Further, we observed that odds of disease mortality decreased with water renewal and increased with the biomass of neighbouring infected oysters under controlled conditions. Based on these findings, we propose mitigation strategies in terms of the regulation of oyster movements between sites, timing of seeding and spatial planning, taking into account seawater temperature and seed origin.